Identification of H3N2 NA and PB1-F2 genetic variants and their association with disease symptoms during the 2014–15 influenza season. Issue 1 (4th June 2021) - Blumenkrantz, Deena R; Mehoke, Thomas; Shaw-Saliba, Kathryn; Powell, Harrison; Wohlgemuth, Nicholas; Liu, Hsuan; Macias, Elizabeth; Evans, Jared; Lewis, Mitra; Medina, Rebecca; Hardick, Justin; Sauer, Lauren M; et al.
Abstract: The 2014–15 influenza season saw the emergence of an H3N2 antigenic drift variant that formed the 3C.2a HA clade. Whole viral genomes were sequenced from nasopharyngeal swabs of ninety-four patients with confirmed influenza A virus infection and primary human nasal epithelial cell cultures used to efficiently isolate H3N2 viruses. The isolates were classified by HA clade and the presence of a new set of co-selected mutations in NA (a glycosylation site, NAg+) and PB1-F2 (H75P). The NA and PB1-F2 mutations were present in a subset of clade 3C.2a viruses (NAg+F2P), which dominated during the subsequent influenza seasons. In human nasal epithelial cell cultures, a virus with the novel NAg+F2P genotype replicated less well compared with a virus with the parental genotype. Retrospective analyses of clinical data showed that NAg+F2P genotype viruses were associated with increased cough and shortness of breath in infected patients.